A Narrative Review on the Risk of Environmental Contaminants in Human Breast Milk and Their Health Implications for Infants in Indonesia - Marlini Marlini; Elizabet Matolisi; Alimin Alimin (Pusat Riset dan Inovasi Nasional, 2026)
Human breast milk is the best source of nutrition and immune protection for infants; however, various environmental contaminants such as pesticides, persistent organic pollutants (POPs), heavy metals, and emerging substances like microplastics have been detected in breast milk worldwide. In Indonesia, exposure risks may be higher in agricultural and industrial areas, potentially affecting milk quality and infant health. This narrative review aims to summarize scientific evidence on environmental contaminants in human breast milk and their possible health effects on infants in Indonesia. Relevant literature published between 2015 and 2025 was collected from PubMed, Scopus, Google Scholar, and national databases, including Garuda and SINTA. The reviewed studies reported the presence of organochlorine pesticides (notably p,p′-DDE), POPs such as PCBs and HCH, heavy metals, and microplastics in breast milk samples. Risk factors included pesticide use, environmental pollution, maternal body fat, and occupational exposure. Potential health impacts on infants involve neurodevelopmental disturbances, endocrine effects, and immune modulation. Nevertheless, evidence consistently shows that the benefits of breastfeeding outweigh the risks of low-level contaminant exposure. In conclusion, environmental contamination of breast milk is a public health issue that remains insufficiently monitored in Indonesia, highlighting the need for improved environmental surveillance, biomonitoring, and integrated policies while continuing to promote breastfeeding.